Efficiency-First Bioacoustic Audio Event Detection Under Resource-Constrained Systems - Magalhães, André M. S.; de Oliveira, Willian D.; Garbossa, Cesar A. P.; Ventura, Ricardo V.; Sousa, Elaine P. M. de (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
Passive acoustic monitoring enables wildlife biodiversity assessment and precision livestock management, yet accurate detectors remain difficult to deploy on resource-limited systems. We present a controlled evaluation of AST, SSAMBA, and MAMBASPEC on two IoT-relevant bioacoustic datasets (aSwine, AnuraSet). MAMBASPEC matches AST within 0.7 pp ROC-AUC w on AnuraSet with 80× fewer parameters and 1,617× fewer FLOPs, while SSAMBA achieves statistically indistinguishable ROC-AUC w at a 12.8× smaller footprint. Friedman tests (p<10 −3 ) and Pareto analysis indicate that MAMBASPEC is the efficiency-first choice under resource constraints, whereas SSAMBA is the accuracy-oriented choice when modest extra latency is acceptable.